Synthesis and biological assessment of indole derivatives containing penta-heterocycles scaffold as novel anticancer agents towards A549 and K562 cells - Zhang, Guanglong; Tang, Zhenhua; Fan, Sili; Li, Chengpeng; Li, Yan; Liu, Weiqin; Long, Xuesha; Zhang, Wenjing; Zhang, Yi; Li, Zhurui; Wang, Zhenchao; Chen, Danping; et al. (Journal of enzyme inhibition and medicinal chemistry, 2023)
Herein, a new series of 2-chloro-N-(5-(2-oxoindolin-3-yl)-4H-pyrazol-3-yl) acetamide derivatives containing 1,3,4-thiadiazole (10a - i) and 4H-1,2,4-triazol-4-amine (11a - r) moiety was designed, synthesised as novel anticancer agents. The antiproliferative activity values indicated that compound 10 b stood as the most potent derivative with IC 50 values of 12.0 nM and 10 nM against A549 and K562 cells, respectively. Mechanism investigation and docking studies of 10 b indicated that it possessed good apoptosis characteristic and dose-dependent growth arrest of A549 and K562 cells, blocked cell cycle into G2/M phase. Interestingly, 10 b suppressed the growth of A549 and K562 cells via modulation of EGFR and p53-MDM2 mediated pathway.